The bodies in the library - Wingate, Marty (Wingate, Marty. First Edition Library mystery, 2019)
"Hayley Burke has landed a dream job. She is the new curator of Lady Georgiana Fowling's First Edition library. The library is kept at Middlebank House, a lovely Georgian home in Bath, England. Hayley lives on the premises and works with the finicky Glynis Woolgar, Lady Fowling's former secretary. Mrs. Woolgar does not like Hayley's ideas to modernize The First Edition Society and bring in fresh blood. And she is not even aware of the fact that Hayley does not know the first thing about the Golden Age of Mysteries. Hayley is faking it till she makes it, and one of her plans to breathe new life into the Society is actually taking flight--an Agatha Christie fan fiction writers group is paying dues to meet up at Middlebank House. But when one of the group is found dead in the venerable stacks of the library, Hayley has to catch the killer to save the Society and her new job"--